Corrosion Resistance of Steel Pipelines under Various Thermal Insulation Materials - Zemlyanko A.S.; Semenov V.S.; Zhukov A.D.; Shuvalova E.A. (Problems of the Regional Energetics, 2021)
The durability of insulation systems for pipelines is determined by the operational resistance of the pipeline material and the design of the insulation system. The issue of studying the corrosion processes of steel pipelines under various heat-insulating materials is relevant. The aim of the work was to study the process of corrosion of steel pipelines under insulating materials of vari-ous nature and porosity. The object of research is pipeline insulation systems. The subject of research is the corrosion processes in various insulation systems. This goal was achieved by car-rying out a set of experimental studies aimed at studying the rate of the corrosion process of the metal of the pipeline, insulated with various materials, with the subsequent calculation of the remaining service life of the pipeline. The most significant results are: the dependence of the corrosion rate and the area of damage of carbon steel on the structure (porosity) of the heat-insulating material, the residual number of ions of water-soluble chlorides. It was found that the maximum corrosion rate of steel under materials with open porosity is 0.29-0.41 mm/year. The increase in the rate of the corrosion process is directly proportional to the increase in the number of chlorine anions in the structure of the material. The smallest area of corrosion damage to the steel surface is observed under materials with open porosity. The significance of the results ob-tained consists in determining the residual life of the pipeline under a heat-insulating layer of various materials.